The Relationship Between Hope and Self-Efficacy and Quarter-Life Crisis in Career Decision-Making Success Among Generation Z - Icha Anggreani Billa Fidha Fadhila; Latifah Nur Ahyani (FKIP - Universitas Riau, 2026)
The transition from late adolescence to early adulthood is a critical developmental stage characterized by identity exploration, career decision-making, and increasing responsibility. Generation Z often faces social and professional challenges due to rapid technological changes, economic uncertainty, and high social expectations, which may trigger a quarter-life crisis marked by anxiety, identity confusion, and career doubts. This study aimed to examine the relationship between hope, self-efficacy, and quarter-life crisis among Generation Z. This research employed a quantitative correlational design using quota sampling. The participants consisted of 121 Generation Z individuals aged 18–30 years residing in Central Java. Data were collected using hope, self-efficacy, and quarter-life crisis scales measured on a four-point Likert scale. Multiple linear regression analysis was used to analyze the data. The results showed a significant relationship between hope, self-efficacy, and quarter-life crisis (R = 0.788; p < 0.01) with an effective contribution of 62.1%. Hope (r = −0.738; p < 0.01) and self-efficacy (r = −0.731; p < 0.01) were negatively correlated with quarter-life crisis. These findings indicate that higher levels of hope and self-efficacy are associated with lower levels of quarter-life crisis.